The Choice of Monetary Policy Regime for Small Open Economies - Kai Leitemo; Øistein Røisland (Norges Bank, 2000)
The paper analyses alternative monetary policy regimes within a simple, estimated macroeconomic model with a traded and a non-traded sector. Two general classes of regimes are considered, inflation targeting and exchange rate targeting, where the latter also includes monetary union. By analysing monetary policy rules within a disaggregated model, the paper adds new insights to the literature on optimal monetary policy rules for open economies. The results suggest that flexible inflation targeting gives lower nominal and real variability than exchange rate targeting or monetary union. The main reason for this is that targeting the nominal exchange rate gives rise to persistent oscillations in the real interest rate and the real exchange rate due to the 'Walter's effect'. Contrary to conventional wisdom, the results suggest that the traded sector is more stable under flexible inflation targeting than under exchange rate targeting.
hdl:11250/2500410
Keywords: E42; E61; E32; 330; inflation targeting; exchange rate targeting; monetary policy; small open economy